PROFIL SENYAWA EKSTRAK DAN FRAKSI BATANG BIDARA LAUT (Strychnosligustrina Blume) DENGAN METODE KLT DAN GCMS - Megawati Megawati; Khairuddin Khairuddin (Universitas Pahlawan Tuanku Tambusai, 2023)
Bidara laut (Strychnos ligustrina Blume) is one of the plants belonging for longaniacea family. Empirically the people of Bima Dompu Bidara laut (Strychnos ligustrina Blume) are used to treat rheumatism, wounds and malaria. This research was conducted identify the profile of the stem Bidara laut compounds by Thin Layer Chromatography and GC-MS. Simplisia the stem Bidara laut extracted by reflux method using ethanol 96%. The results of this study obtained rendamen of 2.7%. Phytochemical screening shows extract containing alkaloids, flavonoids, saponins and tannins. Thin layer chromatography testing of the positive ethyl acetate fraction containing saponins and tannins, the positive n-hexan fraction containing flavonoids and saponins, the positive methanol fraction containing saponins. The results of identification using GC-MS obtained Sucrose, 3-O-Methyl-d-glucose, n-Hexadecanoicacid, Hexadecanoicacid, ethyl ester, Oleicacid, Hexadecanoicacid, 2-hydroxy-1 (hydroxymethyl) ethyl ester, 9-Octadecenoic acidacid (Z) -, 2-hydroxy-1-1 (hydroxymethyl) ethyl ester, and Stigmasterol. Keywords: Strycnos ligustrina Blume, Identification, Extract Fraction, Thin layer chromatography, GC-MS